Methylene blue adsorption of chitosan/nano‐TiO2 films prepared by 3D printing method. Issue 3 (20th June 2021) - Dung, Hoang Tran; Chinh, Nguyen Thuy; Lu, Le Trong; Hoang, Thai
Abstract: This paper presents the preparation of chitosan/nano‐TiO2 films with different contents of nano‐TiO2 by 3D printing technology. The ink solution for printing was prepared by dissolution of chitosan in 1 % acetic acid before dispersing nano‐TiO2 in the chitosan solution by ultrasonic method. The investigated nano‐TiO2 contents were of 3 and 5 wt.% in comparison with chitosan weight. The obtained chitosan/nano‐TiO2 films were characterized by infrared spectroscopy (IR), field emission scanning electron microscopy (FESEM), and ultraviolet‐visible spectroscopy (UV‐Vis) methods. Besides, the water adsorption ability and moisture content in these films were also evaluated. The chitosan/nano‐TiO2 films were used for adsorption of methylene blue in aqueous. The research results confirmed that the chitosan/nano‐TiO2 films are promising adsorbents for removal of coloring matter.